Impact of orange essential oil on enteric methane emissions of heifers fed bermudagrass hay - Jiménez Ocampo, Rafael; Montoya Flores, María Denisse; Pamanes-Carrasco, Gerardo; Herrera-Torres, Esperanza; Arango, Jacobo; Estarrón-Esponosa, Mirna; Aguilar Pérez, Carlos Fernando; Araiza-Rosales, Elia E.; Guerrero Cervantes, Maribel; Ku-Vera, Juan Carlos (Frontiers Media, 2022)
In this study, the effects of orange essential oil (OEO) on the rumen fermentation, nutrient utilization, and methane (CH₄) emissions of beef heifers fed a diet of bermudagrass (Cynodon dactylon) were examined. In addition, in vitro and in situ experiments were conducted. The in vitro experiment consisted of three treatments: control (CTL, no OEO), OEO1 (0.25% OEO), and OEO2 (0.5% OEO). The forage to concentrate ratio was 70:30 (dry matter [DM] basis) in all treatments. No changes in pH, proportions of volatile fatty acids, and the acetate:propionate ratio were observed (P > 0.05). The addition of 0.25% OEO resulted in a reduction in CH₄ production (mL/g) relative to the control (P < 0.05). In the in situ experiment, 5 g of total mixed ration (CTL, OEO1, and OEO2) were incubated for 6, 12, 24, 48, and 72 h. Potential and effective degradability were not affected by OEO supplementation (P > 0.05). In the in vivo study, six crossbred beef heifers (Bos indicus × Bos taurus), fitted with rumen cannulas, were assigned to three different treatments: no additive (CTL), 0.25% OEO (OEO1), and 0.5% OEO (OEO2) in a replicated 3 × 3 Latin square (21-day periods). Heifers were fed at 2.8% body weight. In vivo CH₄ production was measured in open-circuit respiration chambers. Reductions in gross energy consumption, apparent total tract digestibility, and rumen valerate concentration were observed for OEO2 compared to the control (P < 0.05). Additionally, decreases in CH₄ emissions (g/day; P < 0.05) and CH4 (MJ gross energy intake/day; P < 0.05) were observed in response to supplementation of 0.5% OEO as compared to the CTL treatment. Thus, supplementation of 0.5% OEO reduced CH₄ emissions (g/day) by 12% without impacting the DM intake of heifers fed bermudagrass hay as a basal ration.